Effects of preparation methods on inherent fabric anisotropy and packing density of reconstituted sand - Kodicherla, S.; Gong, G.; Fan, L.; Loo Chin Moy, Charles; He, J. (2018)
© 2018, © 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license. This paper investigates the effects of different preparation methods (dry tamping, moist tamping, dry pluviation and wet pluviation) on inherent fabric anisotropy of reconstituted sand samples in the laboratory. An image analysis approach was used to quantify the inherent fabric anisotropy in terms of the vector magnitude based on a second-order fabric tensor. In addition, the effects of reconstituted soil sample preparation methods on the void ratio and density index were investigated. This study shows that the specimens prepared by pluviation methods possess more pronounced inherent fabric anisotropy than those by tamping methods. Among all the methods considered in this investigation, the dry pluviation method provided the highest degree of inherent fabric anisotropy. It is shown that the mass-flow and drop height does not effectively influence the packing density. Also, it has been found that no significant effect on void ratio is observed while using different tamping methods, which may be attributed to the fact that the sand used in this study is less well graded. In addition, it is found that the increase in the height of tamper leads to an increase in packing density or a decrease in relative density, with an approximately linear relationship.